2013
DOI: 10.1021/cs400207c
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation State of Ce in CeO2-Promoted Rh/Al2O3Catalysts during Methane Steam Reforming: H2O Activation and Alumina Stabilization

Abstract: The cerium oxidation state in ceria-doped Rh/Al 2 O 3 catalysts during the methane steam reforming (MSR) reaction was determined by in situ X-ray absorption spectroscopy and online mass spectrometry at 773 K. The catalysts were characterized by electron microscopy and X-ray diffraction. The oxidation states of rhodium and cerium during MSR are related. A total of 25% of Ce 4+ reduces to Ce 3+ under a CH 4 /H 2 O/He flow when the catalyst is active in MSR (773 K). A slight reoxidation occurs when the catalyst i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 60 publications
1
48
0
Order By: Relevance
“…5 In oxygendeficient oxides, cations in two oxidation states (3+ and 4+) are both present. 10 In heterogeneous catalysis, nanoparticles with a high surface area density are of great importance. 6 The oxygen storage capacity is essential for many applications of ceria based materials.…”
Section: Introductionmentioning
confidence: 99%
“…5 In oxygendeficient oxides, cations in two oxidation states (3+ and 4+) are both present. 10 In heterogeneous catalysis, nanoparticles with a high surface area density are of great importance. 6 The oxygen storage capacity is essential for many applications of ceria based materials.…”
Section: Introductionmentioning
confidence: 99%
“… 60,61. In the former, the characteristic white line (indicated as C) corresponds to the 2p 2/3 → (4f 1 )5d electronic transition.…”
mentioning
confidence: 99%
“…Besides as catalyst, ceria (CeO 2 ) prevents alumina from sintering and stabilizes supported nano-sized precious metals such as rhodium, palladium and platinum, which are very important for the enhancement of TWCs activity. 15 Rh/γ-Al 2 O 3 -CeO 2 system had been also investigated as catalyst for the methane steam reforming 16 and the oxidation of methyl tert-butyl ether. 11 In particular, γ-Al 2 O 3 is often used as a support of ceria and noble metals since compared to the other aluminum oxides it features higher catalytic activity due to its structural characteristics and its acid-base properties.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Alumina is a basic component of TWCs and it is widely used in heterogeneous catalysis 9,10 as a support in the refining and petrochemical industries. 17 Shi 18 For Rh/CeO 2 /Al 2 O 3 catalytic system Duarte et al 16 recently reported that, when a reduced sample containing a significant fraction of Ce 3+ ions is exposed to oxygen only part of the Ce 3+ species are converted to Ce 4+ , while a substantial amount of cerium ions remains in oxidation state +3. 12,13,14 CeO 2 /γ-Al 2 O 3 catalysts are also efficient for the dehydrogenation of ethane to ethylene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation